2020
DOI: 10.1111/cob.12370
|View full text |Cite
|
Sign up to set email alerts
|

Low‐carbohydrate interventions for adolescent obesity: Nutritional adequacy and guidance for clinical practice

Abstract: SummaryLow‐carbohydrate dietary patterns are re‐emerging as a popular method of weight reduction. However, their nutritional adequacy to meet the needs of growing adolescents should be considered. This study aimed to design theoretical low‐carbohydrate meal plans for clinical use in the management of adolescent obesity and assess nutritional adequacy. Meal plans were created for three levels of carbohydrate restriction (≤30, ≤50 and ≤120 g/day) without energy, protein or total fat restriction. Nutrient analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Theoretical meal plans for a modified carbohydrate/higher protein diet, IER utilising 3 days/week of VLED, 37 and low carbohydrate approaches at three levels of carbohydrate restriction (<30 g/day; <50 g/day; <120 g/day), 33 have shown that achieving nutritional adequacy is possible. That said, achieving energy restriction and nutritional adequacy relies on the inclusion of nutrient dense foods, such as vegetables (particularly for low carbohydrate and IER approaches), dairy foods and animal‐based protein choices.…”
Section: Considerations For Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical meal plans for a modified carbohydrate/higher protein diet, IER utilising 3 days/week of VLED, 37 and low carbohydrate approaches at three levels of carbohydrate restriction (<30 g/day; <50 g/day; <120 g/day), 33 have shown that achieving nutritional adequacy is possible. That said, achieving energy restriction and nutritional adequacy relies on the inclusion of nutrient dense foods, such as vegetables (particularly for low carbohydrate and IER approaches), dairy foods and animal‐based protein choices.…”
Section: Considerations For Clinical Practicementioning
confidence: 99%
“…Theoretical meal plans support nutritional adequacy, 33 however have not been tested in practice. Limited evidence of psychosocial outcomes in adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coconut flour and seaweed are also commonly used low carbohydrate alternatives. As with any restrictive diet, low carbohydrate diets can impact nutrient intake including thiamine, iron, calcium and fibre intakes (Jebeile et al, 2020 (Feinman et al, 2015). Studies in people with T1D who are not following a low carbohydrate diet show they eat approximately 43%-45% energy from carbohydrate, which is slightly less than the general population (Gilbertson et al, 2018;Helgeson et al, 2006).…”
Section: Low Carbohydrate Dietsmentioning
confidence: 99%
“…References utilised: Eisler et al, (2000), Food and Agricultural Organisation of the United Nations (2020), Gallagher et al (2019), Hart et al (2011), Hay et al (2014, Jebeile et al (2020), Leow et al (2018, Ozier & Henry (2011), Reiter & Graves (2010, Smart et al (2018), and Waterhous and Jacob (2011). Ozier & Henry, 2011;Reiter & Graves, 2010;Royal College of Psychiatrists, 2005;Smart et al, 2018;Waterhous & Jacob, 2011).…”
Section: Sourcementioning
confidence: 99%